PERUBAHAN LAJU KOROSI AKIBAT TEGANGAN DALAM DENGAN METODE C-RING - Rusianto, Toto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Stress Corrosion Craking (SCC) generally attack to metals (steel) under internal stress. Fastener could arised internal stress to material that fastened, such as plat or other material. The experiment to observed SCC could used C-Ring method as standard ASTM G38-01(2007). Fastener and base material that made C-ring corroded in sea water with various stresses that was arrised by fastener. The result of research showed that hardness of spesimen (fastener and C-ring) was increase with increase in stress, the hardness indicated there were internal stress in spesimen. Corrosion rate for spesimen was increase with increase in stress, the higher corrosion rate at spesimen of C-ring for arrised stress 256 kg was 24,20 MPY. and lower arrised stress 69 kg was 19,14 MPY. The spesimen of fastener for arrised stress 256 kg was 7,97 MPY. and lower arrised stress 69 kg was 6,89 MPY. Duration experiment time were 9 day.